2015
DOI: 10.2147/ijn.s82029
|View full text |Cite
|
Sign up to set email alerts
|

GX1-conjugated poly(lactic acid) nanoparticles encapsulating Endostar for improved in vivo anticolorectal cancer treatment

Abstract: Tumor angiogenesis plays a key role in tumor growth and metastasis; thus, targeting tumor-associated angiogenesis is an important goal in cancer therapy. However, the efficient delivery of drugs to tumors remains a key issue in antiangiogenesis therapy. GX1, a peptide identified by phage-display technology, is a novel tumor vasculature endothelium-specific ligand and possesses great potential as a targeted vector and antiangiogenic agent in the diagnosis and treatment of human cancers. Endostar, a novel recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“… 15 Recently, several tumor-specific CPPs have also been developed, such as Pep42 (CTVALPGGYVRVC) for melanomas, NRG (Asn-Gln-Arg) and cRGD [Arg-Gly-Asp-D-Phe-(NMeVal)] for angiogenic blood vessels, and iRGD (CRGDK/RGPD/EC) for various tumors (e.g., prostate cancer, breast cancer, and pancreatic adenocarcinomas). 4 16 17 18 19 20 21 Peptide iRGD could specifically bind to αv integrin in tumor tissue, and then cleaved by protease and exposed to a motif (R/K/XXR/K) for binding to NRP-1, which could mediate penetration into tissues and cells. 3 Conjugation to iRGD significantly improved the sensitivity of tumor-imaging agents and enhanced the activity of antitumor drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 Recently, several tumor-specific CPPs have also been developed, such as Pep42 (CTVALPGGYVRVC) for melanomas, NRG (Asn-Gln-Arg) and cRGD [Arg-Gly-Asp-D-Phe-(NMeVal)] for angiogenic blood vessels, and iRGD (CRGDK/RGPD/EC) for various tumors (e.g., prostate cancer, breast cancer, and pancreatic adenocarcinomas). 4 16 17 18 19 20 21 Peptide iRGD could specifically bind to αv integrin in tumor tissue, and then cleaved by protease and exposed to a motif (R/K/XXR/K) for binding to NRP-1, which could mediate penetration into tissues and cells. 3 Conjugation to iRGD significantly improved the sensitivity of tumor-imaging agents and enhanced the activity of antitumor drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have attempted to conjugate anticancer drugs to some tumor-homing molecules [e.g., GX1-rmhTNFα, GX1-conjugated poly (lactic acid) nanoparticles], and these efforts have resulted in more effective antitumor activity than antitumor drugs alone in GC. 7 21 …”
Section: Discussionmentioning
confidence: 99%
“…Animals were euthanized 4 h or 8 h post-injection, and major organs and bone samples were collected and visualized with the IVIS-200 imaging system. The signal-to-noise ratio (SNR) was obtained as previously described 41 using the following equation: SNR = η A / η B , where η A and η B are the total radiant efficiency of organs from aptamer-injected and control mice, respectively. Tumor samples were frozen and processed for confocal fluorescence microscopy to detect Cy5-labeled aptamers.…”
Section: Methodsmentioning
confidence: 99%
“…It should also be noted that functionalized PLA nanoparticles accumulated better and resulted in a higher fluorescence signal than free fluorophore, IRdye 800CW, alone. 194 It was found that the BODIPY fluorophores synthesized by Kim and colleagues could be successfully encapsulated in silica (SiO 2 ) nanoparticles. Then the surface of the silica nanoparticles could be modified to have an arginineglycine-aspartic (RGD) peptide that would selectively target α v β 3 integrin, which lead to enhanced fluorescence imaging with higher signal to background ratios when compared to the free fluorophores alone.…”
Section: Targetingmentioning
confidence: 99%